Rights of Nature (in relation to the right to nature) - Tassin Wallace, Catalina (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
This work intends to analyze two ways to protect nature, on the one hand «right to nature» and on the other «rights of Nature». From the first model, nature is safeguarded by attributing certain rights to another entity, specifically the human being; from the second, Nature is recognized as a legal subject. Both positions imply different arguments and discussions, which operate in view of a certain type of protection, aims and positions. Taking into account the above, this work seeks to correct the following affirmation: the legal figure of nature as the holder of rights is an unresolved issue. It is a totally defined matter, it only depends on whether nature is recognized as active (Nature) or understood as a receptive object of action (nature).This work intends to analyze two ways to protect nature, on the one hand «right to nature» and on the other «rights of Nature». From the first model, nature is safeguarded by attributing certain rights to another entity, specifically the human being; from the second, Nature is recognized as a legal subject. Both positions imply different arguments and discussions, which operate in view of a certain type of protection, aims and positions. Taking into account the above, this work seeks to correct the following affirmation: the legal figure of nature as the holder of rights is an unresolved issue. It is a totally defined matter, it only depends on whether nature is recognized as active (Nature) or understood as a receptive object of action (nature).